Screening of xylanolytic aspergillus fumigatus for prebiotic xylooligosaccharide production using bagasse - Carvalho, Ana Flavia Azevedo [UNESP]; de Oliva Neto, Pedro [UNESP]; de Almeida, Paula Zaghetto [UNESP]; da Silva, Juliana Bueno; Escaramboni, Bruna [UNESP]; Pastore, Glaucia Maria (Faculty of Food Technology and Biotechnology - University of Zagreb, 2015)
Sugarcane bagasse is an important lignocellulosic material studied for the production of xylooligosaccharides (XOS). Some XOS are considered soluble dietary fi bre, with low caloric value and prebiotic eff ect, but they are expensive and not easily available. In a screening of 138 fungi, only nine were shortlisted, and just Aspergillus fumigatus M51 (35.6 U/mL) and A. fumigatus U2370 (28.5 U/mL) were selected as the most signifi cant producers of xylanases. These fungi had low ß-xylosidase activity, which is desirable for the production of XOS. The xylanases from Trichoderma reesei CCT 2768, A. fumigatus M51 and A. fumigatus U2370 gave a signifi cantly higher XOS yield, 11.9, 14.7 and 7.9 % respectively, in a 3-hour reaction with hemicellulose from sugarcane bagasse. These enzymes are relatively thermostable at 40-50 °C and can be used in a wide range of pH values. Furthermore, these xylanases produced more prebiotic XOS (xylobiose and xylotriose) when compared with a commercial xylanase. The xylanases from A. fumigatus M51 reached a high level of XOS production (37.6 %) in 48-72 h using hemicellulose extracted from sugarcane bagasse. This yield represents 68.8 kg of prebiotic XOS per metric tonne of cane bagasse. In addition, in a biorefi nery, aft er hemicellulose extraction for XOS production, the residual cellulose could be used for the production of second-generation ethanol.
Keywords: Bagasse; Lignocellulosic materials; Xylanases; Xylooligosaccharides